Asian Maritime Power in the 21st Century : Strategic Transactions China, India and Southeast Asia - Sakhuja, Vijay (Book collections on Project MUSE., 2011)
Maritime power has been a key defining parameter of economic vitality and geostrategic power of nations. The first decade of the twenty-first century has witnessed the rise of China and India as confident economic powers pivoting on high growth rates, exponential expansion of science, technology and industrial growth. Sequel to their steadily growing economic clout has been the emphatic resurgence of their maritime power evident in maritime shipping, port development and the concomitant expa ... Maritime power has been a key defining parameter of economic vitality and geostrategic power of natio.